1986
DOI: 10.1159/000124639
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Effects on Plasma Vasopressin and Oxytocin Concentrations Elevated by Histamine, Nicotine, Isoproterenol and an Acute Increase in [NaCl] in Cerebrospinal Fluid

Abstract: Endogenous opioid peptides inhibit secretion of oxytocin during dehydration, hemorrhage and parturition and attenuate release of vasopressin by tail electroshock. Diverse agents were used to stimulate the hypothalamo-neurohypophysial system to investigate the hypothesis that if oxytocin (or vasopressin) release were inhibited by opioid peptides regardless of the stimulus, the site of opiate action may be in the final common pathway (i.e. the magnocellular neuron) or on pituicytes in the neural lobe. Using male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Potentiation of neurohypophyseal OT secretion in rats by the opioid antagonist naloxone is known to occur in re sponse to cellular dehydration, hypovolemia, parturition, restraint, and perhaps suckling [3,8,15,16,20,21]. Our re sults now indicate that the elevation of plasma OT levels produced by systemic injection of CCK and LiCI similarly is potentiated by naloxone.…”
Section: Discussionsupporting
confidence: 54%
“…Potentiation of neurohypophyseal OT secretion in rats by the opioid antagonist naloxone is known to occur in re sponse to cellular dehydration, hypovolemia, parturition, restraint, and perhaps suckling [3,8,15,16,20,21]. Our re sults now indicate that the elevation of plasma OT levels produced by systemic injection of CCK and LiCI similarly is potentiated by naloxone.…”
Section: Discussionsupporting
confidence: 54%
“…In non-pregnant, conscious rats, naloxone has no effect upon the basal plasma concentration of oxytocin, indicating little or no endogenous opioid restraint of basal secretion. In contrast, from about day 10 of pregnancy until term (day 21), naloxone injections elevate oxytocin release, most markedly at term, reflecting active restraint of secretion by endogenous opioids (Hartman et al 1986;Douglas et al 1993b). …”
Section: Central Regulation Of Oxytocin Neurones By Endogenous Opioidsmentioning
confidence: 99%
“…A growing body of evidence suggests that at least one aspect of OT regulation is sub served by endogenous opioid pathways [9,10], Opioid peptides are localized within magnocellular OT-synthesizing neurons [11,12], and opiate receptors have been demonstrated both in the neural lobe of the pituitary [13,14] and in the supraoptic and paraventricular nuclei of the hypothalamus [15]. Treatment with opioid antago nists such as naloxone results in a pronounced increase in the spontaneous firing activity of OT neurons and en hanced pituitary release of OT in response to a variety of stimuli, both in vivo and in vitro [16][17][18][19], Such studies have indicated that both the cell bodies and nerve termi nals of OT neurons are potential sites at which endoge nous opioid peptides may inhibit OT release.…”
mentioning
confidence: 99%